Long-term impact of manuring on soil organic matter quality indicators under field cropping systems - Yadav, Rajendra Kumar; Purakayastha, Tapan Jyoti; Kumar, Dhiraj; Jha, Prakash Kumar; Mahala, Deep Mohan; Yadav, Dinesh Kumar; Khan, M. A.; Singh, Surendra; Singh, Shikha; Vara Prasad, P. V. (Frontiers in Environmental Science, 2023)
Soil organic matter (SOM) quality is the major driving force for nutrient cycles impacting productivity of cropping systems. Identification of sensitive indicators and developing metrics to assess SOM quality is a major challenge under field conditions. Data from a continuing long-term experiment since 2005 at Modipuram, India, was analyzed with key objectives to (1) observe the long-term effect of vermicompost/crop residues alone or in conjunction with NPK chemical fertilizers on crop yield and quality of SOM, (2) identify and develop SOM quality indicators (SOMQI) by encompassing sensitive indicators, and (3) predict system productivity by using SOMQI under rice (Oryza sativa L.)-potato (Solanum tuberosum L.)-wheat (Triticum aestivum L.) (RPW), and maize (Zea mays L.)-potato-onion (Allium cepa L.) (MPO) cropping systems. The treatments comprised of 100% NPK fertilizer; 100% N from vermicompost (N-VC); 50% NPK from fertilizer+50% N from VC; 100% NPK from fertilizer + crop residue (CR); 100% N from VC+CR. Results showed that continuous application of 100% N-VC and 100% N-VC+CR for eight years considerably increased the soil's particulate organic matter carbon (POM-C), light fraction organic matter carbon (LFOM-C) and nitrogen (LFOM-N), dissolved organic carbon (DOC) and nitrogen (DON), as well as the available N (AN), available P (AP) and available S (AS) over control. Principal component analysis (PCA) identified AN, POM-C, LFOM-C:N and DON in RPW and AN, POM-C, microbial biomass carbon (MBC), and LFOM-C:N in MPO cropping system as sensitive SOM quality indicators for development of SOMQI. Under MPO cropping system, results were more pronounced with 100% N-VC and 50% NPK+50% N-VC at 0-15 cm soil depth. Furthermore, at 15-30 cm depth, the effect was more prominent in 100% NPK+CR over other treatments. Overall MPO cropping system exhibited better SOMQI than RPW system. Rice, wheat, and maize yields increased significantly under different fertilizer treatments with organic or inorganic amendments. Substitution of fertilizer N with organic sources showed comparable yields as obtained under 100% NPK treatment. Partial substitution of chemical fertilizers either by VC and/or CR enhanced the SOM quality and productivity under both cropping systems. Use of PCA based SOMQI can be helpful in assessing SOM quality.